Estudo da obtenção de hidrogênio por eletrólise utilizando água residual da indústria do biodiesel - Leal, Maria Luiza Madeiro Barros (2024)
This study aims to investigate hydrogen production through alkaline electrolysis with addition of glycerol to examine the utilization of industrial residues in enhancing the generation of the targeted gas. Thus, experiments were conducted using an alkaline electrolyzer with two different concentrations of the electrolyte potassium hydroxide (1 and 2 mol L-1), along with the addition of residual biodiesel water (glycerol + water + KOH) at variable glycerol concentrations (3.5 and 5%). Scanning Electron Microscopy (SEM), cyclic voltammetry, and chronoamperometry techniques were employed to evaluate the suitable concentration of glycerol with electrolyte. Furthermore, the efficiency of the electrolyzer and the yield of hydrogen were calculated to identify the most satisfactory conditions. The results revealed superior performance in the electrolytic solution containing 1 mol L-1 of KOH and 5% glycerol, generating 87.26 mL of hydrogen in 30 minutes of reaction, with a process efficiency of 72.8% and a yield of 71.8%.